Hospital avoidance: an integrated community system to reduce acute hospital demand. (2019) - McGeoch, Graham; Shand, Brett; Gullery, Carolyn; Hamilton, Greg; Reid, Matthew
Abstract: Background: Growth in emergency department (ED) attendance and acute medical admissions has been managed to very low rates for 18 years in Canterbury, New Zealand, using a combination of community and hospital avoidance strategies. This paper describes the specific strategies that supported management of acutely unwell patients in the community as part of a programme to integrate health services. Intervention: Community-based acute care was established by a culture of close collaboration and trust between all sectors of the health system, with general practice closely involved in the design and management of the services, and support provided by hospital specialists, coordination and diagnostic units, and competent informatics. Introduction of the community-based services was aided by a clinical guidance website and an education programme for general practice teams and allied health professionals. Outcomes: Attendance at EDs and acute medical admission rates have been held at low growth and, in some cases, shorter lengths of hospital stay. This trend was especially evident in elderly patients and those with ambulatory care sensitive or chronic disorders. Conclusions: A system of community-based care and education has resulted in sustained gains for the Canterbury health system and freed-up hospital resources. This outcome has engendered a sense of empowerment for general practice teams and their patients.